Peforma Abnormalitas, Pertumbuhan dan Kelangsungan Hidup Larva Ikan Jelawat (Leptobarbus hoevenii Blkr) Yang Dipelihara Pada Media Air Dengan Jumlah Titik Aerasi Berbeda - Arifin, M Yusuf; Harianto, Eko; Dilla, Risma (Universitas Batangahari Jambi, 2024)
The low oxygen content in the rearing medium causes the larvae of jellyfish to become abnormal, growth is disturbed, and the survival rate is low. The study used a Complete Random Design (RAL) with 4 (four) treatments, namely A: 1 (one) aeration point, B: 2 (two) aeration points, C: 3 (three) aeration points, D: 4 (four) aeration points. Each treatment was carried out 3 times. The results showed that the difference in the number of aeration points given during the rearing of jellyfish larvae had a real effect on the abnormality and performance of the growth of larvae (Leptobarbus hoevenii Blkr). The best treatment for this study was treatment A with the number of aeration points used as much as 1 aeration point for the maintenance of jellyfish larvae (Leptobarbus hoevenii Blkr) in an aquarium with an Absolute Weight Growth (PBM) value of 0.492gr/head, Absolute Length Growth (PPM) 2.97cm/head, abnormality rate of 0.83%, Survival Rate